A Hierarchical 3D Nanostructured Microfluidic Device for Sensitive Detection of Pathogenic Bacteria. Issue 35 (26th July 2018) - Jalali, Mahsa; AbdelFatah, Tamer; Mahshid, Sahar Sadat; Labib, Mahmoud; Sudalaiyadum Perumal, Ayyappasamy; Mahshid, Sara
Abstract: Efficient capture and rapid detection of pathogenic bacteria from body fluids lead to early diagnostics of bacterial infections and significantly enhance the survival rate. We propose a universal nano/microfluidic device integrated with a 3D nanostructured detection platform for sensitive and quantifiable detection of pathogenic bacteria. Surface characterization of the nanostructured detection platform confirms a uniform distribution of hierarchical 3D nano‐/microisland (NMI) structures with spatial orientation and nanorough protrusions. The hierarchical 3D NMI is the unique characteristic of the integrated device, which enables enhanced capture and quantifiable detection of bacteria via both a probe‐free and immunoaffinity detection method. As a proof of principle, we demonstrate probe‐free capture of pathogenic Escherichia coli ( E. coli ) and immunocapture of methicillin‐resistant‐ Staphylococcus aureus (MRSA). Our device demonstrates a linear range between 50 and 10 4 CFU mL −1, with average efficiency of 93% and 85% for probe‐free detection of E. coli and immunoaffinity detection of MRSA, respectively. It is successfully demonstrated that the spatial orientation of 3D NMIs contributes in quantifiable detection of fluorescently labeled bacteria, while the nanorough protrusions contribute in probe‐free capture of bacteria. The ease of fabrication, integration, and implementation can inspire future point‐of‐care devices based on nanomaterial interfaces for sensitive and high‐throughput optical detection. Abstract : A nanostructured platform embedded in a fluidic sample delivery is developed for sensitive detection of pathogenic bacteria. The integrated device features a detection platform based on hierarchical 3D nano‐/microislands (NMI) of gold, enabling direct capture, and rapid and quantifiable detection of bacteria. The performance of the device is studied by probe‐free detection of pathogenic Escherichia coli and immunodetection of methicillin‐resistant‐ Staphylococcus aureus .